Skull base aspergillosis in an immunocompetent elderly man with early response to steroid. Issue 1 (28th November 2018) - Sarkar, Pamela; Price, Christopher; Fish, Mark; Bennetto, Luke
Abstract : We report the case of a previously well 80-year-old man who presented with subacute bilateral painful optic neuropathy with initial response to corticosteroids but ultimately progressed to a fatal skull base syndrome. Initial presentation of steroid-responsive painful bilateral posterior optic neuropathy, preliminary normal enhanced MRI, normal cerebrospinal fluid and inflammatory markers indicated atypical optic neuritis. However, this progressed to a bilateral orbital apex syndrome with ophthalmoplegia and evidence of abnormal skull base enhancement on subsequent MRI. Biopsy of radiologically abnormal dura was non-diagnostic and negative for fungal stains. He deteriorated and died 8 months after initial presentation. At postmortem, fungal skull base infection was diagnosed. This case demonstrates that chronic skull base fungal infection can: (1) present in elderly immunocompetent patients, (2) show initial improvement with corticosteroids and (3) evade diagnosis on biopsy. We encourage a high index of suspicion for fungal skull base infection in similar cases.